2017
DOI: 10.1016/j.gmit.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic stromal tumor resected by laparoscopic surgery

Abstract: We report a case of microcystic stromal tumor (MCST) resected by laparoscopy. MCST is a very rare ovarian tumor with distinctive microcystic features and a characteristic stromal tumor immunopheno-type. The present case was a 26-year-oId woman who underwent laparoscopic surgery for suspected endometrial cyst of the left ovary. The mass was 8 cm in size and contained bloody fluid, and after attempting cystectomy, we eventually performed left salpingo-oophorectomy with a final postoperative pathological diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This neoplasm exhibits some distinctive morphological and immunochemical features. In most cases, the tumor has variable islands of monotonous round to ovoid cells with microcystic spaces and has diffusely strong immunoreactivity for CD10, vimentin, WT-1, and β-catenin (nuclei) and is negative for EMA (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). These features are readily apparent and permit the correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This neoplasm exhibits some distinctive morphological and immunochemical features. In most cases, the tumor has variable islands of monotonous round to ovoid cells with microcystic spaces and has diffusely strong immunoreactivity for CD10, vimentin, WT-1, and β-catenin (nuclei) and is negative for EMA (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). These features are readily apparent and permit the correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…CT shows a heterogeneous mass with hypo- and hyperattenuating areas, while FDG uptake on PET corresponds to solid cellular components. Although MR images were not obtained in our patient, Murakami et al reported MRI findings in a 26 year old with ovarian MST, revealing a predominantly cystic lesion with high-signal intensity on T2-weighted imaging and isosignal intensity on T1-weighted imaging ( Murakami et al, n.d. ). These imaging findings reliably reflect underlying histopathologic characteristics and may aid in early recognition of these benign neoplasms.…”
Section: Discussionmentioning
confidence: 68%
“…Microcystic stromal tumors fall within the group of pure stromal tumors, which also includes fibromas, thecomas, Leydig and steroid cell tumors ( Kurman, 2014 ). Ovarian MST, like other sex cord-stromal tumors, has generally been found in younger patients with reported ages ranging from the 20s to the 60s ( Oliva, 2014 ; Horta, 2015 ; Murakami et al, n.d. ). These tumors are typically unilateral, often <5 to 10 cm in size without associated hormone-mediated symptoms and with a favorable clinical course that has not yet been associated with malignancy ( Oliva, 2014 ; Irving et al, 2015 ; Murakami et al, n.d. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Microcystic Stromal Tumors Microcystic stromal tumors are very rare and present in patients between the ages of 20 and 60. 23 On immunostaining, microcystic stromal tumors have shown the expression of CD10, vimentin, and Wilms tumor 1, while sex cord-stromal markers (α-inhibin and calretinin) and epithelial membrane antigen are negative. 24 Nuclear expression of β-catenin occurs in microcystic stromal tumors.…”
Section: Pure Stromal Tumors Fibromasmentioning
confidence: 99%